Influential Factors Affecting Sea Transportation Services to Enhance Customer Satisfaction: Faktor-faktor yang Mempengaruhi Layanan Transportasi Laut guna Mendukung Kepuasan Pengguna Jasa - Taharuddin; Hartati, Diah Vitaloka; R, Sulastriani; Nurmala, Eka; Mursalin (PT. Alpha Trianguli Australis, 2024)
Indonesia, as an archipelagic country, of course, sea transportation is the main supporting element in facilitating the transfer of people or goods from one place to their final destination. Optimizing sea transportation services is something that must be done by the government and the private sector if they want to create a reliable and competitive transportation ecosystem. This article reviews the factors that influence sea transportation services, namely sea transportation human resources, sea transportation facilities, and sea transportation infrastructure, a literature study on transportation management. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Sea transportation human resources influence sea transportation services; 2) Sea transportation facilities influence sea transportation services; and 3) Sea transportation infrastructure influences sea transportation services.